The feminization of agriculture? Economic restructuring in rural Latin America - Carmen Diana Deere (United Nations Research Institute for Social Development (UNRISD), 2005)
The main trends associated with the economic crisis, neoliberal restructuring, and the growth of rural poverty rates in Latin America include a continued diversification of rural household income-generating strategies, an increase in the number of household members seeking off-farm employment, and the increased participation of rural women as both own-account and wage workers in the agricultural as well as non-agricultural sectors. While methodological problems persist in analysing changes in rural women's work over time, the dominant trend in the region over the past several decades has been towards the feminization of agriculture. The growth in women's agricultural wage employment has been concentrated in the non-traditional agro-export sector favoured under neoliberalism: specifically, in the production and packing of fresh vegetables, fruits and flowers for Northern markets, what now constitutes Latin America's leading agricultural export rubric. In many countries women and children make up half or more of the field labour for these crops, while women constitute the vast majority of the workers in the packing houses geared to the export market. Nonetheless, the characteristics of this employment, principally its temporary, seasonal and precarious nature, have made it difficult to capture quantitatively in national censuses and household surveys. The essay analyses the role of gender-segmented labour markets in increasing the demand for female labour, as well as the significance of women's increased participation in wage labour for female empowerment. There is also evidence, stronger for some countries than others, of a feminization of smallholder production, as growing numbers of rural women become the principal farmers-that is, own-account workers in agriculture. This phenomenon is associated with an increase in the proportion of rural female household heads; male absence from the farm, in turn related to growing male migration and/or employment in off-farm pursuits; and the decreased viability of peasant farming under neoliberalism. There is little question that the principal factor driving these trends is the need for rural households to diversify their livelihoods. The combination of growing land shortage, economic crises and unfavourable policies for domestic agriculture has meant that peasant households can no longer sustain themselves on the basis of agricultural production alone. The response to the crisis of peasant agriculture has been an increase in the number of rural household members pursuing off-farm activities. Whether these are male, female, or include both genders, depends on a myriad of factors, with household composition and the stage of the domestic cycle, and the dynamism and gendered nature of local, regional and international labour markets, being among the most important.
Keywords: 330